Effect of nitrogen and mineral composition of the high-concentrated wort made from starch-containing raw materials on the cultivation of yeast - Shiyan, Peter; Mudrak, Tatiana; Kyrylenko, Roman; Kovalchuk, Svitlana (My University, 2017)
The feasibility of enriching highly concentrated wort from starch-containing raw materials with nitrogen and mineral nutrition for yeast cells has been theoretically substantiated and experimentally confirmed. The effect of nitrogen nutrition in the form of amine and ammonia nitrogen, as well as mineral nutrition in the form of nanoparticles and metal ions, has been studied. It has been experimentally established that the addition of nitrogen and mineral nutrition allows obtaining a high concentration of yeast cells with high physiological and biochemical activity, as well as reducing the duration of yeast generation. Теоретично обґрунтовано та експериментально підтверджено доцільність збагачення високонцентрованого сусла із крохмалевмісної сировини азотним та мінеральним живленням для дріжджових клітин. Досліджено вплив азотного живлення в якості амінного та аміачного азоту, а також мінерального живлення в якості наночастинок та іонів металів. Експериментально встановлено, що додавання азотного і мінерального живлення дозволяє отримати високу концентрацію дріжджових клітин, з високою фізіолого-біохімічною активністю, а також скоротити тривалість дріжджегенерування.
Keywords: yeast cell; highly-concentrated wort; dry substances; yeast-generation; nanoparticles of metals; дріжджова клітина; висококонцентроване сусло; сухі речовини; дріжджегенерування; наночастинки металів; кафедра біотехнології продуктів бродіння і виноробства; кафедра готельно-ресторанної справи